KONTRIBUSI PEMBELAJARAN QAWA>ID NAHWU TERHADAP KETERAMPILAN MEMBACA MAHASISWA IAIN BONE - Amir B; Muhammad Rasmi (Institut Agama Islam Negeri (IAIN) Bone, 2019)
To learn and understand Arabic, the must first to know is about the Arabic grammar, or so called qawa 'id or nahwu. This study aims to determine the importance of learning qawa 'id nahwu in improving reading skills of IAIN Bone students. This research is classified as a descriptive qualitative research. Data collection was carried out through observation, interviews, and documentation. Interviews were conducted involving six Arabic language lecturers at IAIN Bone. The Arabic lecturers at IAIN Bone applied discussion and demostration method in teaching qawa 'id nahwu. The discussion method applied in nahwu learning makes a significant contribution in making students more creative, active, and provides opportunities for them to freely ask and convey ideas.Keywords: Qawaid Nahwu, Reading skill, Arabic learning